RFLP analysis of genetic variation in species of section Arachis, genus Arachis (Leguminosae) - Gimenes, M. A.; Lopes, C. R.; Galgaro, M. L.; Valls, JFM; Kochert, G. (Kluwer Academic Publ, 2002)
Four A-genome species of the genus Arachis ( A. cardenasii, A. correntina, A. duranensis, A. kempff-mercadoi), three B genomes species ( A. batizocoi, A. ipaensis and A. magna), the AABB allotetraploid A. hypogaea (cultivated peanut) and introgression lines resulting from a cross between A. hypogaea and A. cardenasii were analyzed by RFLP. The A genome species (cytologically characterized by the presence of a small chromosome pair 'A') were closely similar to each other and shared a large number of restriction fragments. In contrast, the B genome species differed more from one another and shared few fragments. The results of this study indicate that the absence of the small chromosome pair is not a good criterion for grouping species of section Arachis as B genome species, since their genome might be quite distinct from the B genome of A. hypogaea. The lowest genetic variation was detected within accessions of A. duranensis (17 accessions), followed by A. batizocoi (4 accessions) and A. cardenasii (9 plants of accession GKP 10017). The high level of genetic variation found in A. cardenasii might indicate that not all accessions of wild species of Arachis are autogamous, as reported for A. hypogaea.
Keywords: Arachis; genetic variation; germplasm; RFLP